Manajemen Pendidikan Karakter di SMA Negeri Teladan Yogyakarta Masa Pandemi Covid-19 - Lia Yuliana (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2022)
This study aims to determine the management of character education in SMA Negeri I Teladan Yogyakarta. This research method uses a qualitative approach. The steps are 1) collecting data through a questionnaire technique); 2) reducing data with the aim of simplifying and categorizing data; 3) presenting data in the form of a mean description; 4) drawing conclusions and 5) compiling research reports, and formulate recommendations for research results. The results of the study show that: 1) the management of character education at SMA Negeri I Teladan Yogyakarta has so far applied management principles, that the character education program at SMA Negeri 1 Yogyakarta is integrated into both curricular and extracurricular; 2) There are obstacles in the implementation, namely the learning system, the understanding of teachers and employees is not yet optimal,) the students' understanding of the importance of character education, and media, equipment, and program support are still lacking so that the implementation of education the character in the class is less than optimal; 3) The efforts made by schools in implementing character education management are the establishment of a character education implementing and monitoring team, teachers are required to carry out assessments concerning character, namely the spiritual and social aspects on an ongoing basis; an evaluation of the development of character education is carried out based on the results of teacher assessments, intensive socialization is carried out to teachers, employees, and students regarding character education programs, and schools seek to support the implementation of character education programs.